Performance and return to sport after injury in professional mixed martial arts. Issue 5 (3rd September 2022) - Kingery, Matthew T; Kouk, Shalen; Anil, Utkarsh; McCafferty, Joseph; Lemos, Connor; Gelber, Jonathan; Gonzalez-Lomas, Guillem
ABSTRACT: Background: Mixed Martial Arts (MMA) is an increasingly popular combat sport incorporating striking and grappling that results in a high incidence of injuries. Objectives: The purpose of this study was to analyze the impact of injuries on the return to sport and post-injury performance of professional MMA athletes. We hypothesize that increased age is associated with lower probability of return to sport and diminished post-injury performance. Methods: Publicly available data (obtained from ESPN.com/MMA, UFC.com, Rotowire.com/MMA) from professional MMA fighters who resigned from fight cards due to injury from 2012 to 2014 were analyzed. Injury history, match history and outcomes, and duration of time to return to professional fighting were recorded and compared to a cohort consisting of uninjured opponents. Results: 454 fighters were included in the analysis. The mean age at the time of injury was 30.0±3.9 years. 94.4% of injured athletes were able to return to professional MMA, and athletes required a mean duration of 6.8±6.7 months between injury and their next professional fight (range 0.3–58 months). There was no significant difference in winning percentage in the post-injury period between the injured group and the uninjured group (p = 0.691). Increased age at the time of injury was associated with the odds of being able to return to professional fighting after injury (OR = 0.822, p = 0.001). Conclusion: In this analysis of publicly available injury data on MMA fighters, there was a high rate of return to professional sport and no evidence of an associated decline in performance following major injury requiring withdrawal from a fight card. Older age at the time of injury was associated with decreased odds of being able to return to professional fighting. With increasing popularity of combat sports, sport-specific prognostic information will help guide and treat specific injuries associated with MMA participation.